2014
DOI: 10.1016/j.jpurol.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cold ischemia for preservation of testicular function during partial orchiectomy in the rat model

Abstract: Objective We hypothesized that cold ischemia during partial orchiectomy would lead to higher serum testosterone levels and preservation of testicular architecture than warm ischemia in a prepubescent rat model. Materials and methods Eighteen prepubescent male Sprague–Dawley rats were randomized to three different surgical groups: sham surgery, bilateral partial orchiectomy with 30 min of cord compression with cold ischemia, or bilateral partial orchiectomy with 30 min of cord compression with warm ischemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Similarly, Heidenreich et al [30] have recommended immersion of the testis in an ice slush solution after occlusion of the cord, to maintain a temperature of 151C to 191C for the duration of the procedure. Ealier studies in rats have shown that warm ischemia for less than 30 minutes does not result in irreversible injury to Sertoli cells, and cold ischemia provides no benefit at 30 minutes [58,59]. In an effort to minimize warm ischemia time, some authors have described delaying clamping of the cord until after tumor localization [12].…”
Section: Operative Techniquementioning
confidence: 99%
“…Similarly, Heidenreich et al [30] have recommended immersion of the testis in an ice slush solution after occlusion of the cord, to maintain a temperature of 151C to 191C for the duration of the procedure. Ealier studies in rats have shown that warm ischemia for less than 30 minutes does not result in irreversible injury to Sertoli cells, and cold ischemia provides no benefit at 30 minutes [58,59]. In an effort to minimize warm ischemia time, some authors have described delaying clamping of the cord until after tumor localization [12].…”
Section: Operative Techniquementioning
confidence: 99%